RELEVANCE OF KUNTOWIJOYO'S PROFETIC SOCIAL SCIENCE WITH ARIF MAFTUHIN'S “BEYOND THE RUKHSAH” IDEA - Awalluddin, Awalluddin (Islamuna: Jurnal Studi Islam, 2025)
ABSTRACT Contemporary social problems require an integrative approach from various academic disciplines to achieve meaningful transformative solutions. This research aims to analyze the relevance of Kuntowijoyo's "Prophetic Social Science" concept to Arif Maftuhin's "Beyond the Rukhsah" concept within the context of Islamic scholarly paradigms concerning the empowerment of persons with disabilities. This study employs a literature research method with a comparative analysis approach to the primary works of Kuntowijoyo and Arif Maftuhin. The results demonstrate significant convergence between the three pillars of Prophetic Social Science—humanization, liberation, and transcendence—with the "Beyond the Rukhsah" paradigm that advocates for an azimah approach in disability jurisprudence, replacing the rukhsah (dispensation) paradigm that tends to be marginalizing. Humanization manifests in efforts to elevate the dignity of persons with disabilities as full subjects in the community, liberation is reflected in the redefinition of Islamic law that is more inclusive, while transcendence strengthens the foundation based on divine values. This research is expected to have implications for opening new epistemological paradigms that integrate empirical-transformative dimensions in Islamic studies, encouraging the formation of theoretical frameworks for the development of a more just, inclusive, and civilized society. ABSTRAK Problematika sosial kontemporer memerlukan pendekatan integratif dari berbagai disiplin keilmuan untuk mencapai solusi transformatif yang bermakna. Penelitian ini bertujuan menganalisis relevansi gagasan "Ilmu Sosial Profetik" Kuntowijoyo terhadap konsep "Beyond the Rukhsah" Arif Maftuhin dalam konteks paradigma keilmuan Islam tentang pemberdayaan penyandang disabilitas. Kajian ini menggunakan metode penelitian kepustakaan dengan pendekatan analisis komparatif terhadap karya-karya primer Kuntowijoyo dan Arif Maftuhin. Hasilnya menunjukkan konvergensi signifikan antara tiga pilar Ilmu Sosial Profetik—humanisasi, liberasi, dan transendensi—dengan paradigma "Beyond the Rukhsah" yang mengadvokasi pendekatan azimah dalam fikih disabilitas, menggantikan paradigma rukhsah (dispensasi) yang cenderung marginalisatif. Humanisasi termanifestasi dalam upaya mengangkat martabat penyandang disabilitas sebagai subjek penuh dalam komunitas, liberasi tercermin pada redefinisi hukum Islam yang lebih inklusif, sementara transendensi memperkuat landasan berbasis nilai ketuhanan. Penelitian ini diharapkan berimplikasi pada terbukanya paradigma epistemologis baru yang mengintegrasikan dimensi empiris-transformatif dalam studi Islam, mendorong pembentukan kerangka teoretis untuk pengembangan masyarakat yang lebih adil, inklusif, dan berkeadaban